Interplay of Microbiome, Oxidative Stress and Inflammation in Health and Disease - Herrera-Quintana, Lourdes; Iturbe-Sanz, Pablo; Olivares-Arancibia, Jorge; Vázquez-Lorente, Héctor; Plaza-Diaz, Julio (Antioxidants, 2026)
The human microbiome plays a crucial role in health, being involved in both physiological and pathological processes. The highly dynamic microbiome composition is shaped by different factors, which also may affect host–microbe interactions. Although this relationship is complex and incompletely understood, the interplay between the microbiome, oxidative stress and inflammation is increasingly recognized. Microbial metabolites and specific probiotic strains contribute to maintaining redox homeostasis through multiple pathways, such as regulating the immune system and inflammatory processes or influencing mitochondrial reactive oxygen species production and antioxidant signaling pathways. Oxidative stress and inflammation, in turn, may affect the microbiome by altering microbial diversity and function. These disturbances are believed to create a vicious cycle that further disrupts homeostasis and promotes the appearance of different diseases. This review synthesizes current evidence on the interplay between the microbiome, oxidative stress, and inflammation, highlighting its relevance to both physiological and pathological states.
Keywords: microbiome; free radicals; redox balance; inflammatory processes; ROS/RNS; redoxomics; microbial metabolites